Developing an instrument model to assess teachers’ creativity in designing and teaching music subject (Harmonia: Journal of Arts Research and Education, 2017)
This paper aims at developing an instrument model to assess teacher’s creativity in designing and teaching music at school. The study was conducted by adapting the approach of Research and Development (RD) from the model designed by Borg and Gall and the cycle model design developed by Cenamo Kalk. The development comprises two stages; the model development and dissemination. The model development encompassed of model planning, model designing, as well as the try out. While, the dissemination stage was done by presenting the research result at a conference. At the end of the study, it was proven that the assessment instrument model used to assess teachers’ creativity in designing and teaching music subject at school had met with the research aim. It was shown from the try out test on the assessment instrument model development that: (1) the assessment material, assessment technique, rater criteria, assessment object, units of observation, competence test process, time allotment, observation process, measurement criteria, as well as the measurement rubric had been considered appropriate and had provenly matched from one to another so that it can be applied well; (2) the reliability of the assessment instrument based on Intraclass Correlation Coefficients/ICC test on consistency and absolute agreement definition type as well as the Generalizability Coefficient had met the criteria.